THE IMPORTANCE OF USING TASK-BASED LANGUAGE TEACHING (TBLT) METHOD IN TEACHING ADULTS - Jabbarova Zuxraxon Davron kizi (International Journal of Literature and Language Studies, 2026)
The increasing demand for effective language instruction has led educators to explore learner-centered approaches that promote meaningful communication and practical language use. Among these approaches, Task-Based Language Teaching (TBLT) has gained considerable attention due to its emphasis on real-life communication and active learner engagement. This article examines the importance of using TBLT in teaching adult learners. Through a review of relevant literature and analysis of pedagogical practices, the study highlights the benefits of TBLT in enhancing communicative competence, learner motivation, and practical language application. The findings suggest that TBLT provides adult learners with authentic opportunities to use language in meaningful contexts, making it a valuable method in adult language